O uso de materiais concretos no ensino da geometria. - ARAÚJO, Regina Dias (Universidade Federal do Tocantins, 2023)
The present work focused on the study of platonic polyhedra, with emphasis on the use of concrete materials for the teaching of Geometry. The intention was to answer the following questions about this topic: How do concrete materials contribute to students' learning in Geometry teaching? To what extent can this Pedagogical tool? What are the strengths and weaknesses of the approach used? The theoretical basis was based on authors who relate the history of Mathematics Geometry, Platonic polyhedrons and concrete materials. To carry out the analysis, this research made necessary the elaboration and development of a workshop entitled "Geometric Solids: Platonic Polyhedra", in which the target audience was composed of students from the ninth grade of Elementary School, from the CAIC School - Jorge Humberto de Camargo, for through theoretical and practical lessons, with the aim of providing students with differentiated classes in order to minimize their difficulties in relation to the content addressed. As a result understand that the use of concrete materials stimulates learning and students are motivated to study mathematics.